2012 9th IEEE International Symposium on Biomedical Imaging (ISBI) 2012
DOI: 10.1109/isbi.2012.6235678
|View full text |Cite
|
Sign up to set email alerts
|

Personalized learning-based segmentation of thoracic aorta and main branches for diagnosis and treatment planning

Abstract: Coarctation of the aorta (CoA), is an obstruction of the aortic arch present in 5 − 8% of congenital heart diseases. For children older than a year, CoA is increasingly treated by aortic stenting instead of surgical repair. In pediatric cardiology, CMR is accepted as the standard non-invasive imaging modality to assess the aortic arch in it's entire spatial context [1]. Interpreting such 3D datasets are required to assess the underlying anatomy during both diagnosis and therapy planning phases. However this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The overall pre-processing pipeline is illustrated in Figure 4. The details of the image segmentation and other geometric pre-processing steps were reported previously 25 , together with a validation study with clinical evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…The overall pre-processing pipeline is illustrated in Figure 4. The details of the image segmentation and other geometric pre-processing steps were reported previously 25 , together with a validation study with clinical evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…In the interest of easing translation of personalized CoA models into wider clinical practice, we set out to meet certain expectations. On this course, we have broadly extended our previous works [23][24][25] with stent segmentation, post-and virtual stenting (VS) hemodynamic models. Thus, our contribution provides:…”
Section: Introductionmentioning
confidence: 99%
“…35 Segmentation of the aorta, including the supra-aortic arteries from MRI, was initially presented in our previous work. 24,25 Multiple groups investigated CoA hemodynamics through computational modeling. Recent studies have suggested that good agreement may be reached between measured and simulated hemodynamic and morphologic indices if subjectspecific boundary conditions are employed.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work on vessel segmentation of the aorta and its main branches, different types of approaches have been used. For instance, approaches based on the Hough transform (e.g., [6]), region growing (e.g., [7]), atlas registration (e.g., [8]), level sets (e.g., [9]), statistical shape models (e.g., [10,11]), machine learning techniques (e.g., [12]), and cylindric intensity models (e.g., [13,14]). However, in previous work often only CTA image data have been used (e.g., [10,7,8,11]), aortic pathologies such as stenoses have often not been considered (e.g., [6][7][8][9]11]), or only the abdominal and descending parts of the aorta are segmented (e.g., [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Fur-thermore, previous segmentation approaches are typically applied to image data from adults whereas work on pediatric image data and follow-up studies can hardly be found. In [12], an approach is proposed for the segmentation of the thoracic aorta in adult and pediatric MRA image data. The approach is based on machine learning techniques using a multi-stage learning and probabilistic boosting-tree.…”
Section: Introductionmentioning
confidence: 99%